PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA PT. SUNGGONG LOGISTICS - Tri Martiani LN Subagiyo (Jurnal Manajemen, 2018)
In the high competition of the forwarder industry, having a big names and a lot of fleets is not enough. Standard customer requirements are always increase. Customer satisfaction is very important for any service company, but some studies show that satisfaction of customers is not enough. Because there is no guarantee that satisfied customers will become loyal customers. Therefore, it is important for service companies to provide the quality of service which expected by the costumers with the competitive price. This research is conducted to analyze the correlation between service quality and price to customer loyalty with customer satisfaction as the intervening variable. This research uses multiple linear regression analysis and using two structural models with SPSS program. The population used is consumer of PT. Sunggong Logistics. While the sample used counted 100 people with sample selection technique using probability sampling. The results indicates that there is a positive and significant influence between service quality to customer satisfaction. There is a positive and significant influence between price and customer satisfaction.There is a positive and significant influence between service quality and price with customer satisfaction. There is no direct positive and significant influence between the quality of Service to customer loyalty. There is a positive and significant direct effect of price on customer loyalty. There is a positive and significant influence between customer satisfaction and customer loyalty.There is a positive and significant influence between service quality, price and customer satisfaction with customer loyalty.